Food away from home of middle-income earners: empirical evidence from the three major cities in Malaysia - Rusli Latimaha; Zakaria Bahari; Nor Asmat Ismail (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia have achieved high income growth and experienced rapid urbanization and changes in socioeconomic and demographic structure. Family income as well as demographic factors influence demand for food away from home. At the same time food service facilities also showed the rapid growth. It is expected that there will be significant changes in food away from home consumption in Malaysia. The objective of this paper is to analyse middle income household expenditure patterns on food away from home in the three major cities of Malaysia (George Town, Kuala Lumpur and Johor Bahru) that have a high cost of living. Therefore, a survey has been carried out in the three cities and the total number of observations used for the estimation was 473 observations. A censored Tobit model was applied to quantify the responsiveness of household expenditure on food away from home. The results indicate that on average, the household income and number of children below 12 years old in the household are the significant factors that affect the household expenditure on food away from home. There is a significant difference between the Chinese and Malays in their spending pattern on food away from home. Meanwhile, family size, gender and age of household head were statistically insignificant. It is recommended that the government should strengthen the enforcement of price control regulations in order to avoid high inflation in food price, as well as monitoring the quality of food served by the sellers in order to encourage people to consume healthy food.